2020
DOI: 10.1108/jedt-02-2020-0055
|View full text |Cite
|
Sign up to set email alerts
|

Compressed earth block reinforced with coconut fibers and stabilized with aloe vera and lime

Abstract: Purpose In recent years, the use of earth as a material applied to construction has been adapted as an attractive alternative to modern concepts. The earth construction technique takes advantage of regional natural resources, among which are earth bricks. The purpose of this paper is to analyze the effect of the addition of coconut fibers and aloe vera on the mechanical properties of compressed earth blocks (CEB). Design/methodology/approach CEBs were manufactured from silty and clay soil (Altamira, Tamaulip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Sustainability 2024, 16, x FOR PEER REVIEW 18 of 30 fibers [153]. Additionally, studies by Prabakar J, Pullen QM, and others [154][155][156] involved the modification of earth with plant fibers such as sisal, corn husks, and coconut fibers, and the analysis revealed that fibers inhibited crack propagation before specimen cracking, resulting in good ductility. Yang et al [157] proposed adding bamboo reinforcement to wall structures and placing wooden pads under rafters to enhance overall mechanical performance.…”
Section: Effect Of Component Optimization On Deformabilitymentioning
confidence: 99%
“…Sustainability 2024, 16, x FOR PEER REVIEW 18 of 30 fibers [153]. Additionally, studies by Prabakar J, Pullen QM, and others [154][155][156] involved the modification of earth with plant fibers such as sisal, corn husks, and coconut fibers, and the analysis revealed that fibers inhibited crack propagation before specimen cracking, resulting in good ductility. Yang et al [157] proposed adding bamboo reinforcement to wall structures and placing wooden pads under rafters to enhance overall mechanical performance.…”
Section: Effect Of Component Optimization On Deformabilitymentioning
confidence: 99%
“…[57] University of Jaffna Sri Lanka [58] Curtin University Australia [59] National Institute of Technology Agartala India [60] National Institute of Technology Agartala India [9] University of Trás-os-Montes e Alto Douro Portugal University of Minho [61] Chandigarh University India [8] University of Minho Portugal University of Trás os Montes e Alto Douro Vila Real [62] Chandigarh University India Guru Ghasidas University [63] Federal University of Rio Grande do Norte (UFRN) Brazil Federal Institute of Education, Science and Technology of Paraíba (IFPB) [64] BMS College of Engineering India [21] University of Biskra Algeria [15] University of Biskra Algeria University of Ouargla University of Djelfa [65] University of Minho Portugal Federal Center for Technological Education "Celso Suckow da Fonseca" (CEFET/RJ) Brazil [66] Indian Institute of Technology Guwahati India [67] University of Moratuwa Sri Lanka University of Ruhuna [23] Instituto Tecnologico de Pachuca Mexico Universidad Autonoma de Tamaulipas Universidad Nacional Autonoma de México [68] Universidad Industrial de Santander Colombia [69] University of Kelaniya Sri Lanka [70] Quaid-e-Awam University of Engineering Pakistan…”
Section: Reference(s) Author(s) Affiliation Country Number Of Authorsmentioning
confidence: 99%
“…Earth blocks manufactured in conjunction with stabilizing agents were introduced to fix these flaws. Traditional stabilizers such as cement [3,5,17,19,20] and lime [19,[21][22][23] have been used extensively in this domain. "Compressed Stabilized Earth Blocks" (CSEBs) are essentially manufactured by mixing a stabilizer in a definite proportion to the soil and then pressing either manually or mechanically.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the use of natural and synthetic fibres to reinforce compressed earth blocks (CEBs) has been evaluated by various researchers. The effect of fibres like vetiver shoot [10], banana fibre [13-14], coconut fibre [15][16], sugarcane bagasse fibre [17][18], cogon fibre [19], jute fibre [20][21], polypropylene [22], rice straw [23], cork granules [24], sisal fibre [25][26], oil palm fibre [27][28][29][30][31][32] among others, on various properties of CEBs have been investigated. The results obtained from their investigations showed that the use of fibres in CEB production led to improved mechanical and durability properties of the blocks.…”
Section: Introductionmentioning
confidence: 99%